MILP branch flow model for concurrent AC multistage transmission expansion and reactive power planning with security constraints - Macedo, Leonardo H. [UNESP]; Montes, Cristiam V. [UNESP]; Franco, John F. [UNESP]; Rider, Marcos J.; Romero, Ruben [UNESP] (Inst Engineering Technology-iet, 2016)
This study presents a mixed-integer linear programming (MILP) model to solve the simultaneous transmission network expansion planning (TNEP) and reactive power planning (RPP) problem. The proposed model considers reactive power, off-nominal bus voltage magnitudes, power losses, multistage expansion, and security constraints. The use of an MILP model guarantees convergence to optimality by using existing classical optimisation methods. In order to validate the approximation performed, the steady-state operation points were compared with those obtained using an AC load flow method. Garver's 6-bus system and a modified IEEE 118-bus system were used to show the precision and efficiency of the methodology. The results indicate that better expansion and generation plans are found by considering RPP simultaneously with the AC TNEP, when the solutions were compared with the plans of the TNEP using the AC model without RPP and the TNEP considering the DC model, with RPP conducted at a subsequent stage.
Keywords: load flow; reactive power; power transmission planning; power system security; integer programming; linear programming; MILP branch flow model; concurrent AC multistage transmission expansion; reactive power planning; security constraints; mixed-integer linear programming; TNEP; simultaneous transmission network expansion planning; reactive power planning problem; RPP problem; off-nominal bus voltage magnitudes; power losses; classical optimisation methods; steady-state operation points; AC load flow method; Garver 6-bus system; modified IEEE 118-bus system